Passing the NBCOT Examination: Preadmission, Academic, and Fieldwork Factors - Sharon D. Novalis; Jill M. Cyranowski; Cathy D. Dolhi (Scholarworks @ WMU, 2017)
All occupational therapy students are required to successfully complete the certification examination administered by the National Board for Certification in Occupational Therapy (NBCOT) before they can practice independently. The need to repeat the examination can result in stress, anxiety, and financial hardship. This paper explores the relationship of preadmission factors, academic and fieldwork performance, and demographic variables to successful first-time attempts on the certification examination for occupational therapists. Data were gathered from 144 student files in a Master of Occupational Therapy (MOT) Program at a single university. Of the sample, 82% passed and 18% failed their first NBCOT test trial. Considered independently, preadmission recommendation letters and writing sample scores, graduate MOT program GPA, lack of MOT program difficulty, fieldwork self-reports, and gender predicted NBCOT certification examination outcomes. When considered together in logistic regression models predicting outcome, this combination of factors correctly predicted 86.2% of student outcomes (or 20% to 32% of the variance in certification examination success), with OT program GPA and preadmission recommendation scores predicting unique outcome variance. This information may be helpful to admissions committees as well as to occupational therapy faculty as they identify strategies and practices to facilitate first-time test taking success on the NBCOT certification examination